QOLP-08. THE LANDSCAPE OF EPILEPSY ASSOCIATED WITH DIFFUSELY INFILTRATIVE GLIOMAS. (12th November 2021) - Drumm, Michael; Templer, Jessica; Bushara, Omar; Unruh, Dusten; Walshon, Jordain; Javier, Rodrigo; McCortney, Kathleen; Burdett, Kirsten; Kurz, Jonathan; Swanson, Geoff; Horbinski, Craig
Abstract: Seizures are among the most prevalent co-morbidities associated with glioma, and pose a serious threat to patients. Our prior work showed that IDH mutation (IDHmut) was associated with much greater seizure frequency at the time of initial glioma diagnosis. However, less is known about the variables that contribute to seizure risk throughout the course of disease. We therefore collected data from 247 patients with grade 2–4 glioma, and determined seizure risk using Kaplan-Meier survival probabilities and multivariable cox regression analyses. Median follow-up of IDH wildtype (IDHwt) and IDHmut glioma patients was 15 months and 36 months, respectively. Incidence of pre-operative seizures for IDHwt and IDHmut patients was 75/168 (45%) and 60/79 (76%), and incidence of post-operative seizures was 70/168 (42%) and 43/79 (54%), respectively. Patients who had a pre-operative seizure had a shorter time to their first post-operative seizure than patients who never had a pre-operative seizure in both IDHwt (P< 0.0001) and IDHmut (P= 0.039) cohorts. Among IDHmut glioma patients, those with subtotal resections developed post-operative seizures faster (median time to first seizure= 9.9 months) than those with gross-total resections (median not reached) (P= 0.0005), but a similar pattern was not observed in IDHwt glioma patients (P= 0.20). Those with IDHmut astrocytomas more quickly developed post-operative seizures (median= 11.1 months), compared to those with IDHwt astrocytomas (24.9 months) or IDHmut oligodendrogliomas (median not reached) (P= 0.033). Tumor progression closely followed post-operative seizures in patients with IDHwt gliomas when either their first post-operative seizure occurred longer than 6 months following resection, or when their post-operative seizures worsened in quality. These data suggest the best predictors of post-operative seizures are as follows: the presence of pre-operative seizures; extent of surgical resection; IDHmut status. These data will help clinicians better manage glioma patients by identifying those at greatest risk of seizures.